A framework for addressing violence and serious crime focused deterrence, legitimacy, and prevention - Braga, Anthony Allan 1969-; Kennedy, David M. 1958- (Cambridge University Press, 2021)
This Element examines an increasingly important community crime prevention strategy - focused deterrence. This strategy seeks to change offender behavior by understanding underlying crime-producing dynamics and conditions that sustain recurring crime problems, and implementing a blended set of law enforcement, community mobilization, and social service actions. The approach builds on recent theorizing on optimizing deterrence, mobilizing informal social control, enhancing police legitimacy, and reducing crime opportunities through situational crime prevention. There are three main types of focused deterrence strategies: group violence intervention programs, drug market intervention programs, and individual offender programs. A growing number of rigorous program evaluations find focused deterrence to be an effective crime prevention strategy. However, a number of steps need to be taken to ensure focused deterrence strategies are implemented properly. These steps include creating a network of capacity through partnering agencies, conducting upfront and ongoing problem analysis, and developing accountability structures and sustainability plans
Title from publisher's bibliographic system (viewed on 22 Feb 2021)
Keywords: Violent crimes / Prevention; Gewaltkriminalität; Prävention; Abschreckung; USA